Del Cary Smith, Ordinances of the City of Port Townsend, Washington, Comprising the General Ordinances of the City, Together with the Private Ordinances Now in Force, at 27, div. 3, § 15 (1890) - (:unkn) unknown (My University, 1890)
Whoever shall fire or discharge any cannon, gun, pistol revolver or any firearm of any description, or shall fire, or explode or set off any squib, firecracker, torpedo or other thing containing powder or other explosive material, without permission from the Mayor or common council so to do, within the city limits, shall, on conviction, be punished by a fine of not less than five nor more than twenty dollars
Keywords: DISCHARGE